Relationship between Nomophobia and Attention among Medical Students in Jakarta - Kevin Tanoto; Eva Suryani; Satya Joewana (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: The advancements in technology in the form of smartphones have made life easier; however, some negative effects have been recorded with regards to the use of smartphone. Among these negative effects are nomophobia, or a phobia of no mobile phone, and lack of attention. This study explored the relationship between nomophobia and attention in medical students.Methods: This was a cross-sectional analytic study on medical students in Jakarta in 2019. The Nomophobia Questionnaire (NMP-Q) was used to measure the level of nomophobia and the Six Letter Cancellation Test (SLCT) was used to measure attention. Data collected were analyzed using a simple linear regression test.Result: There was a weak negative relationship between the severity of nomophobia and attention (r=.161). However, nomophobia score was a very weak predictor for attention with an adjusted r-squared score of .021.Conclusions: Nomophobia does not necessarily affect the attention of medical students. Excessive mobile phone use does cause nomophobia and lack of attention. Therefore, smartphones need to be used wisely.